CROSS-SECTION RESTORATION FOR VALIDATING INTERPRETATION IN POOR SEISMIC IMAGE, STUDY CASE: BETARA HIGH, JAMBI SUB-BASIN - Rahmadi Hidayat, Rahmadi Hidayat (Departmen Teknik Geologi, 2015)
Study area is located at Betara High of Jambi Sub-basin, northernmost area of South Sumatera Basin. Seismic re-study become quite active recently, especially in less-explored area surrounding Betara Complex as main hydrocarbon field in the area. However, poor seismic data due to Plio-Pleistocene syn-inversion requires better justification for seismic interpretation to reduce uncertainty and geological risk. This research proposed an alternative validation method for seismic interpretation, especially in horizon picking, utilizing cross-section restoration based on geometrical point of view. Fault-horizon network and flexural slip unfolding were carried out in interpreted regional NNE-SSW seismic line to define cross-section restoration. Slip movement of fault-horizon network, controlled in Hz-4, of Fault 1 (1055 m) and Fault 2 (400 m) produced near perfect joint-bed of all horizons on each segments. Flexural slip unfolding also depicted similar true vertical thickness (TVT) across segments of all intervals (Near GUF, UTAF and LTAF). This method indicated good geometrical validity in seismic interpretation. In visualizing TVT map as validation, cross-section restoration gives better image than conventional flattening method because it can resolve thickness ambiguity in fault zone. In tectonically inverted area, it is critical to resolve this problem in order to avoid irregular interpolation value near to fault zone.